2021
DOI: 10.1093/jmicro/dfab001
|View full text |Cite
|
Sign up to set email alerts
|

A photoswitchable fluorescent protein for hours-time-lapse and sub-second-resolved super-resolution imaging

Abstract: Reversibly photoswitchable fluorescent proteins (RSFPs) are a class of fluorescent proteins whose fluorescence can be turned on and off by light irradiation. RSFPs have become essential tools for super-resolution (SR) imaging. Because most SR imaging techniques require high-power-density illumination, mitigating phototoxicity in cells due to intense light irradiation has been a challenge. Although we previously developed an RSFP named Kohinoor to achieve SR imaging with low phototoxicity, the photoproperties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Since the discovery of the first RSFP called asFP595 (tetrameric) in 2000 [ 15 ], many RSFPs with monomeric states, long emission wavelengths, high photostability, fast maturation, and high photoswitching quantum yield (PQY) have been developed [ 16 , 17 , 18 , 19 ]. In general, they can be classified into three categories: negative, positive, and decoupled types [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the first RSFP called asFP595 (tetrameric) in 2000 [ 15 ], many RSFPs with monomeric states, long emission wavelengths, high photostability, fast maturation, and high photoswitching quantum yield (PQY) have been developed [ 16 , 17 , 18 , 19 ]. In general, they can be classified into three categories: negative, positive, and decoupled types [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics were improved to some extent in Kohinoor, a variant based on Padron. The recently reported Kohinoor2.0 exhibits a 2.9-fold higher molecular brightness than Kohinoor, but its switching fatigue has not been investigated and it has not been used for RESOLFT nanoscopy . Kohinoor has been used for a demonstration of point-scanning RESOLFT nanoscopy, but we found that Kohinoor is still prone to switching fatigue.…”
Section: Introductionmentioning
confidence: 64%
“…The recently reported Kohinoor2.0 exhibits a 2.9-fold higher molecular brightness than Kohinoor, but its switching fatigue has not been investigated and it has not been used for RESOLFT nanoscopy. 28 Kohinoor has been used for a demonstration of point-scanning RESOLFT nanoscopy, but we found that Kohinoor is still prone to switching fatigue. However, resistance against switching fatigue is a key requirement for one-step RESOLFT imaging.…”
Section: Introductionmentioning
confidence: 82%
“…rsEGFP2 can be switched from a non-fluorescent "OFF" state to a green fluorescent "ON" state by irradiation with 405 nm, while 488 nm are used for fluorescence excitation and to simul-taneously switch rsEGFP2 back to the "OFF" state. Alternatively developed RSFPs come with high stability for long-term time-lapse image acquisition (Kohinoor2.0), far red-shifted wavelength properties (rsFusionRed3) or dual-color modes for pulse-chase setups and other more elaborate investigations (mIrisFP) [122][123][124]. A fairly extensive list of currently available RSFPs for RESOLFT microscopy has been published recently [125].…”
Section: Fp-based Tags and Sensors Of Tomorrow's Investigationsmentioning
confidence: 99%